Detection of Malware Propagation in Sensor Node and Botnet Group Clustering Based on E-mail Spam Analysis - Taejin Lee; Hesun Cho; Haeryong Park; Jin Kwak (International Journal of Distributed Sensor Networks)
Cyber incidents are increasing continuously. More than 200,000 new malicious codes appear, with more than 30,000 malicious codes distributed each day on average. These cyber attacks are expanding gradually to the social infrastructure (nuclear energy, power, water, etc.) and smart sensor networks. This paper proposes a method of detecting malware propagation in sensor Node and botnet clustering automatically by analyzing e-mails. More than 80% of spam e-mails are generated by the Node infected with malicious code, using various methods to avoid filtering such as direct-to-MX, fake Received header, and open relay vulnerability. This paper proposes a scheme that detects those types accurately, including a clustering method that targets the URL included in the e-mail body, e-mail subject, attached file, and hosting server, to detect the botnet group infected with the same malicious code. The proposed method recorded about 85% zombie IP detection rate when spam e-mails distributed in a commercial environment were analyzed. When applied to the portal site that delivers 10 million e-mails, the proposed technology is expected to detect at least 150,000 zombie Nodes each day. If advanced measures are taken against the detected zombie Nodes, the spread of cyber attack damages can apparently be reduced.